Utilization of eco Enzymes as a Natural Disinfectant on Floors - Ummu Kultsum; Mulyadi Mulyadi; Rasman Rasman (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2025)
With the increasing amount of waste, there is a need for proper waste management techniques that are safe for the environment and life. Eco enzymes are made from the fermentation of organic waste derived from fruit and vegetable waste. The principle of the process of making eco enzymes is similar to the process of making compost as a growth medium so that the final product produced can be obtained in liquid form. The floor is one of the places that can be associated with the transmission of various diseases or the spread of microorganisms. Efforts that can be made by keeping the floor clean are by providing disinfectants when mopping. The purpose of this study was to determine whether eco enzymes can be utilized as a floor disinfectant in reducing the number of germs. This research is a pre-experiment type using one group of subjects, namely the floor and examining the number of germs before and after applying eco enzymes to the floor. How to do it by mopping the floor with eco enzyme liquid on the ceramic floor at home and swabbing the floor before and after mopping. The results showed that from the examination of the floor before the application of eco eznym in the morning, the results were 3,0 × 103 colonies/cm2, at noon as many as 4,4 × 103 colonies/cm2, and in the afternoon as many as 5,1 × 102 colonies/cm2. Examination of the number of germs on the floor after the application of eco enzymes in the morning obtained a result of 1,4 × 101 colonies/cm2, at noon as much as < 1,0 × 100 colonies/cm2, and in the afternoon as much as < 1,0 × 100 colonies/cm2. The conclusion in this study states that the decrease in the number of germs on the floor after administration reaches 99.9% and eco enzymes can be utilized as a floor disinfectant